Heap Bioleaching of Refractory Arsenic Gold Concentrates - Cheng, Dong-Hui; He, Jiang-Tao; Li, Guo-Bin (Asian Journal of Chemistry, 2012)
In this work, we pretreated refractory arsenic gold concentrate, obtained from the Shaanxi Pangjiahe mine located in Feng county, Shaanxi, China, by heap bioleaching with Acidithiobacillus ferrooxidans (A.f.). The purpose of this research was to evaluate the feasibility of heap bioleaching on refractory gold concentrate. The samples with an agglomerate agent were bio-leached within a temperature range of 15-28 ºC for periods of 60 d, 132 d and 306 d, respectively, in leaching column. Then the residues were cyanide leached. The highest gold extraction rate increased from 39.97 %, which is the gold extraction rate from the direct cyanidation process, to 88.66 %. Our results demonstrate that the Au extraction rate was linear with the As extraction rate. The redox potential of Fe3+/Fe2+ is the primary potential in the leaching solution and the T.f. activity varied periodically with inhibition and accommodation. Heap bioleaching can probably be applied on refractory gold concentrate. Further study should be carried out to determine ways to shorten the bioleaching time.